Profesionalisme Guru Paud Dalam Menciptakan Lingkungan Belajar Yang Berbasis Bermain Dan Kreativitas Anak - Hasbi Hasbi (FKIP UNSULTRA, 2025)
The professionalism of PAUD teachers is a fundamental aspect in creating a fun, creative learning environment that aligns with the developmental characteristics of early childhood. This literature review aims to examine the role and professional competencies of PAUD teachers in developing a play-based learning environment that encourages children's creativity. The research was conducted by analyzing various scientific articles published between 2019 and 2024 that discussed teacher professionalism, play approaches, and the development of children's creativity. The results of the study indicate that PAUD teacher professionalism encompasses four main aspects: pedagogical, personality, social, and professional competencies. Professional teachers are able to design learning activities that stimulate children's exploration, imagination, and curiosity through educational games and warm interactions. In addition, professionalism is also reflected in teachers' ability to innovate in the use of contextual learning media, such as interactive digital games, educational game tools (APE), and project-based activities. This study concludes that strengthening PAUD teacher professionalism through ongoing training and reflection on teaching practices is key to building a meaningful and creative learning environment for early childhood.